2008
DOI: 10.1021/bm701043c
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Extracellular Polymeric Substances Produced by Escherichia coli Using Infrared Spectroscopic, Proteomic, and Aggregation Studies

Abstract: The aim of this study was twofold: first, to characterize the free extracellular polymeric substances (EPS) and bound EPS produced by Escherichia coli during different growth phases in different media, and then to investigate the role of the free EPS in promoting aggregation. EPS was extracted from a population of E. coli MG1655 cells grown in different media composition (Luria-Bertani (LB) and Luria-Bertani with the addition of 0.5 w/v% glucose at the beginning of the growth phase (LBG)) and at different grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
156
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(171 citation statements)
references
References 60 publications
10
156
0
Order By: Relevance
“…Next, the EPS content was evaluated via the sugar/protein ratio so as to compare those for the individually grown E. coli isolate and E. coli grown in the microbial community. The EPS sugar and protein contents were evaluated because they have been reported as indicators of cell conditions (81). It was observed that the sugar/protein ratio was greatly enhanced in the presence of the microbial community (0.10 to 0.23) over that for E. coli O157:H7 in the Haznedaroglu study (0.03) (78).…”
Section: Discussionmentioning
confidence: 99%
“…Next, the EPS content was evaluated via the sugar/protein ratio so as to compare those for the individually grown E. coli isolate and E. coli grown in the microbial community. The EPS sugar and protein contents were evaluated because they have been reported as indicators of cell conditions (81). It was observed that the sugar/protein ratio was greatly enhanced in the presence of the microbial community (0.10 to 0.23) over that for E. coli O157:H7 in the Haznedaroglu study (0.03) (78).…”
Section: Discussionmentioning
confidence: 99%
“…However, considerably less is known about the effect of biological factors on photocatalytic inactivation of bacteria. One biological factor that is likely to influence photocatalytic activity is the presence of capsular bacterial extracellular polymeric substances (EPS), which typically comprise polysaccharides and proteins (13).…”
mentioning
confidence: 99%
“…Located at or outside the cell surface, EPS have many functions, including facilitating bacterial adhesion, providing a protective barrier against environmental stresses, maintaining hydration, and storing nutrients (13). The protective function has been reported to significantly increase bacterial tolerance to antibiotics and disinfectants both by limiting the transport of biocides and via a direct reaction with the EPS (14,15).…”
mentioning
confidence: 99%
“…Cell sedimentation assay. The cell sedimentation rate was quantified using the assay described by Eboigbodin and Biggs (25) and Fu et al (26). Cells were grown in YPD liquid medium with or without 0.1 g/ml doxycycline (for transcriptional repression) and 2.5 mM L-cysteine or ascorbic acid.…”
Section: Methodsmentioning
confidence: 99%